In Nature, There Is Only Diversity - Michael R. McLaren (American Society for Microbiology, 2018)
ABSTRACT Microbial ecology has been transformed by the advent of high-throughput marker gene and metagenomic sequencing methods. These tools provide expansive descriptions of microbial communities, but the descriptions are framed in terms of molecular objects, such as 97% ribosomal operational taxonomic units (OTUs), rather than biological objects, such as species. A recent study by A. B. Chase and colleagues (mBio 8:e01809-17, 2017, https://doi.org/10.1128/mBio.01809-17) explores the so-called microdiversity within the Curtobacterium OTU, the most abundant OTU in a leaf litter community. Perhaps unsurprisingly, they find that some important ecologic traits, such as drought response, are coherent within the OTU, but that others vary significantly. Here we discuss their findings in relation to the more general issue of how molecular tools can be effectively used to study microbial ecology. We specifically note the need for investigators to choose the right molecular methods for their biological problem, as nature does not respect the limitations and conventions associated with our methods.